Effectiveness and Efficiency of Corral Traps, Drop Nets and Suspended Traps for Capturing Wild Pigs (Sus scrofa) - Gaskamp, Joshua A. (Animals (Basel), 2021)
SIMPLE SUMMARY: New or revised techniques are being developed to improve management of expanding populations of invasive wild pigs. In southern Oklahoma, we set out to evaluate the success of various trap types: a conventional corral trap design, drop nets developed for capturing other wildlife, and recently developed suspended traps. Suspended traps removed 88.1% of the estimated population of wild pigs, whereas drop nets removed 85.7% and corral traps removed 48.5%. Suspended traps removed one pig for every 0.64 h invested in control, whereas drop nets had a 1.9 h investment per pig and corral traps had a 2.3 h investment per pig. Drop nets and suspended traps removed more of the wild pig population, mainly through whole sounder removal. The suspended trap required the least amount of time per pig removed because of real-time notifications and remote actuation from a cell phone. Drop nets and suspended traps offer greater control and time savings with the use of remote technology, making intensive, large-scale removal of pigs possible. Now, with commercially available technology, corral traps also can be configured to be user operated with real-time monitoring and trapping. ABSTRACT: Strategic control and eradication programs for wild pigs (Sus scrofa) are being developed to help curtail the expanding populations of this invasive, alien species. Drop nets and corral traps have a long history of capturing a multitude of wildlife species, so we evaluated the effectiveness and efficiency of these traps for controlling wild pigs in southern Oklahoma. We also developed and evaluated a suspended metal trap that provided real-time monitoring and deployment to capture animals. Effectiveness of each trap type was estimated as the proportion of pigs removed from the total population, whereas efficiency was calculated based on catch per unit effort (CPUE) (i.e., the number of person hours per pig removal). During 3 years of study (2010–2012), we removed 601 pigs, 296 using drop nets, 60 using corral traps, and 245 using suspended traps. Suspended traps removed 88.1% of the estimated population, whereas drop nets removed 85.7% and corral traps removed 48.5%. CPUE was 0.64 person hours/pig using suspended traps followed by 1.9 person hours/pig for drop nets and 2.3 person hours/pig for corral traps. Drop nets and suspended traps were more effective at removing a large proportion of the population (>85%), mainly through whole sounder removal, but the suspended trap with real-time notifications was the most efficient trap type, requiring fewer person hours to operate.